(1) LGBTQ+ AV Collections: Full Text Corpus - (:unkn) unknown (My University, 2021)
This file includes all of the LGBTQ+ collections that were identified as part of the project, and organizes the text output as well as associated metadata in an Excel spreadsheet. Transcripts can be found in Column B, "Text."